Rheological properties of Indian coffee plum (Flacourtia jangomas) pulp in steady and dynamic shear at different temperatures. Issue 1 (1st January 2021) - Nath, Debarshi; Barbhuiya, Rahul Islam; Singh, Sushil Kumar; Dwivedi, Madhuresh
ABSTRACT: Indian coffee plum ( Flacourtia jangomas ) is an underutilized fruit with many great nutritional and medicinal value generally available in the northeastern part of India. Although rheological study of different fruit pulps have been studied till now, however no such study has been undertaken on Indian coffee plum. The present study was aimed to evaluate the steady-state shear and viscoelastic rheological properties of Flacourtia jangomas (F. jangomas) pulp as function of temperature in the range 20 to 80°C using dynamic oscillatory viscometry, as well as applicability of Cox-Merz rule. Under steady-state shear tests, the shear stress versus shear rate data were adequately fitted to the Bingham model (R 2 = 1) for too low shear rate (0.1to 1.0 s −1 ) and Power law model (R 2 > 0.83) for moderate shear rate (1.0 to 100 s −1 ). Oscillatory shear data of the fruit pulp showed weak gel behavior where loss modulus exceeded the value of storage modulus. The power modified Cox-Merz rule was tested for all temperature and found applicable for lower temperatures. These results could be beneficial for future studies on food properties and industries. Abstract : uf0001